A Community-Based Trial on The Comparison of Efficacy, Safety and Cost Effectiveness of Ferrous Sulphate and Ferrous Ascorbate for Anaemia in Pregnancy In Madhya Pradesh, India - Manju Toppo; Meena, Jeewan S; Gour, Devendra; Kamble, Mugdha; Keerthana S; Ankit Chandak; Sarjan Singh; Bhunjiya, Nainshree; Ravindra Singh (National Journal of Community Medicine, 2023)
Background: Anaemia has significant impact on health of the fetus as well as that of mother. Increased need of iron during pregnancy especially after 2nd trimester makes iron supplementation mandatory. Ferrous ascorbate is known to exist intact inside the gastrointestinal tract due to the stable chelation of iron with ascorbate. This compound does not dissociate due to any of the food inhibitors. The aim is to study the effectiveness of Ferrous Ascorbate and Ferrous sulphate in terms of compliance and cost effectiveness of management of anaemia in pregnancy. Methodology: Study design: Quasi Experimental study, Study area: District Vidisha, Study participants: Pregnant women of first trimester registered during the study period in the selected Anganwadis/ Gram Arogya Kendra (GAK), Sample size: 240 antenatal mothers. Results: Baseline mean haemoglobin was 11.31±1.05 gm/dl. The mean increase in Ferrous Sulphate was 0.55 gm/dl, and in Ferrous ascorbate was 1.27 gm/dl. Ferrous Sulphate was less compliant than Ferrous ascorbate, and has higher efficacy and lesser side effects. Only Rs. 10.2 additional cost per antenatal mothers for increase of ≥1gm% in Hb will be borne by government if Ferrous Sulphate is replaced by Ferrous Ascorbate. Conclusions: Study results show statistically significant difference in rise of haemoglobin amongst the antenatal mothers consuming Ferrous ascorbate over Ferrous Sulphate.